P04.04 Chlamydia infection in males and females reporting sex with partners with chlamydia. (13th September 2015) - Huffam, S; Chow, EPF; Fairley, CK; Hocking, J; Peel, J; Chen, M
Abstract : Background: Justification for presumptive treatment for a sexually transmitted infection depends in part on the underlying prevalence of that infection among those reporting exposure. To examine these data for chlamydia we aimed to ascertain the proportion infected with chlamydia, and factors predictive of infection, amongst females, heterosexual males and men who have sex with men (MSM) presenting to a sexual health service reporting sexual contact with a chlamydia infected partner. Methods: Patients included were those attending the Melbourne Sexual Health Centre from October 2010 to September 2013. Proportions testing positive amongst females, heterosexual males, and MSM reporting sexual contact with a chlamydia infected partner were ascertained. Demographic and behavioural data obtained using computer assisted self-interview were analysed to determine predictive factors. Results: Of the 491 female, 808 heterosexual male, and 268 MSM chlamydia contacts, the proportion diagnosed with chlamydia were 39.9% (95% CI 35.7–44.3), 36.1% (95% CI 32.9–39.9), and 23.5% (95% CI 18.8–29.0) respectively. Female chlamydia contacts were more likely to have chlamydia if age ≤24 (AOR 1.86, 95% CI 1.12–3.10) or if they reported inconsistent condom use during vaginal sex with a regular male partner (AOR 2.5, 95% CI 1.12–6.14). Heterosexual male contacts were more likely to have chlamydia if age ≤26 (AOR 1.70, 95% CI 1.26–2.30) or if they had a regular female sexual partner (AOR 1.42, 95% CI 1.06–1.91). In MSM urethral chlamydia was diagnosed in 8.8%, rectal chlamydia in 20.2%, and in 3.9% at both sites. MSM were more likely to have chlamydia if they had a regular male sexual partner (OR 2.12 95% CI 1.18–3.81). Conclusion: This study of female, heterosexual male and MSM presentations with self-reported chlamydia contact provides insight as to their likelihood of infection. The data may inform policy and individual clinical decision making regarding presumptive treatment of chlamydia contacts. Disclosures: No potential conflicts of interest.